Three-dimensional positional relationship between impacted mandibular third molars and the mandibular canal - Yun Yang; Dong-Yu Bao; Can Ni; Zhen Li (BMC, 2023)
Abstract Objective To observe the three-dimensional positional relationship between impacted mandibular third molars (IMTMs) and mandibular canal close contacts using cone beam computed tomography (CBCT). Methods A total of 101 patients with IMTMs were selected who met the diagnostic criteria for 142 teeth (no bone wall imaging area between IMTMs and the mandibular canal, a high-density bone cortical imaging area only, or a ≦1 mm bone imaging area). The parameters of the rotating CBCT anode were set as follows: 110 kV, 40-50 mA; the focal point and exposure field were set as 0.3 mmh and a high-resolution zoom, respectively; the exposure time and image layer thickness were set as 5.4 s and 0.25 mm. Three-dimensional reconstruction was performed, and the position of the mandibular canal through the IMTM area was observed continuously from the coronal, horizontal and sagittal planes. Results We found that the mandibular canal was interrupted below the third molar (TM) in 85 cases, accounting for 59.86% of all cases. The mandibular canal was located below the buccal and lingual curvatures in 33 and 19 cases, respectively, accounting for 23.23% and 19%. In addition, a small number of mandibular canals were also located on the buccal side of the mandibular molars (2.82%). We also found one case of direct insertion of the mandibular third molar (MTM) into the mandibular canal. In addition, the mandibular canal passed through the IMTM region with 125 close contacts at the roots (88.03%); 14 mandibular canals were in contact with all teeth and 3 were in contact with the crown. Conclusion The use of CBCT can provide a dynamic and comprehensive understanding of the three-dimensional positional relationship of the mandibular alveolar nerve canal passing through the IMTM area, providing a high clinical reference value when extracting IMTMs and reducing the risk of injury to the inferior alveolar nerve.